Excursos sobre a “Linguagem Emancipatória”: o experimentalismo americano e a génese de uma nova poiesis visual e sonora - Roberto, Isabella Alessandra Cortada (Via Panoramica: Revista de Estudos Anglo-Americanos / A Journal of Anglo-American Studies, 2020)
It was in the field of literary visual and spatial experimentations, the matter of which all poetry is made of, that the morphological, phonetical, syntactical and semiological research is still being carried on. The dissolution of the significant and the signified is regarded as a subversion of the syntax, the semantics and the spelling of the language, an invention of new ways of writing and the demand for new ways of reading, for an active engagement of the reader in the process of decoding the text. Reading and interpreting this hybrid composition, in which the verbal and the non-verbal become intricate, requires the understanding that we are before a playful game, at once rational and experimental, dealing with all the dimensions of the linguistic sign: visual, sound and meaning. We aim at a more amplified conceptual theory frame by resorting to authors varying from different artistic schools from the fifties up to the eighties, such as the New York School, the Black Mountain College and the L=A=N=G=U=A=G=E School. Subversion is the key-code.